2020
DOI: 10.21203/rs.3.rs-40914/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tamil version of the Fear of COVID-19 Scale

Abstract: Background: The seven-item Fear of COVID-19 Scale (FCV-19S) assesses severity of fear of COVID-19 (novel coronavirus). The present study translated the scale into Tamil and tested its psychometric properties so that the scale can be used in Tamil-speaking populations. Methods: The FCV-19S was translated into Tamil following a forward-backward translation procedure. Using an online-based survey, 95 participants completed the Tamil version of the FCV-19S alongside questions about demographic information. Psychom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Routine reversal creates insecurity and uncertainty while physical distancing, weakens the physical network of individuals and triggers anxiety reactions (Tsipropoulou et al 2020). A recent study showed that feelings of anxiety and depressive symptoms, distress and sleep problems were typical signs of the COVID-19 pandemic (Bharatharaj et al 2020). One of several important reasons that during the pandemic could mean increased anxiety and stress is the threat of COVID-19 and, more specifically, the fear of becoming infected or infecting precious persons (Tzur Bitan et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine reversal creates insecurity and uncertainty while physical distancing, weakens the physical network of individuals and triggers anxiety reactions (Tsipropoulou et al 2020). A recent study showed that feelings of anxiety and depressive symptoms, distress and sleep problems were typical signs of the COVID-19 pandemic (Bharatharaj et al 2020). One of several important reasons that during the pandemic could mean increased anxiety and stress is the threat of COVID-19 and, more specifically, the fear of becoming infected or infecting precious persons (Tzur Bitan et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that feelings of anxiety and depressive symptoms, distress and sleep problems were typical signs of the COVID-19 pandemic (3). One of several important reasons for increased anxiety and depression is the threat of COVID-19 and, more specifically, the fear of becoming infected (4).…”
Section: Introductionmentioning
confidence: 99%
“…Specialists have recently developed a 7-item unidimensional scale that assesses fear of COVID-19 (Ahorsu et al 2020). Various studies have confirmed the validity of the Fear of COVID-19 Scale in different cultures (Alyami et al 2020;Bharatharaj et al 2020;Doshi et al 2020;Mahamid et al 2020;Perz et al 2020;Satici et al 2020a;Soraci et al 2020;Winter et al 2020). However, just because such an instrument has been validated in many cultures does not mean that it can be translated and used elsewhere; it is necessary to ensure that the concept and measurement of fear of COVID-19 makes sense in a given culture.…”
mentioning
confidence: 99%
“…The FCV-19S has Arabic, Bangla, Chinese, English, Ethiopian Amharic, French, Greek, Hebrew, Indian, Italian, Japanese, Malay, Russian, Spanish, Tamil, and Urdu versions. Cronbach's alpha for the were between .80 to .89 [7,12,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36].…”
Section: Measurementioning
confidence: 99%